The Relation between Photosynthesis, Respiration, and Crassulacean Acid Metabolism in Leaf Slices of Aloe arborescens Mill - Denius, Homer R. (1972)
Leaves and leaf slices from Aloe arborescens Mill. were used to study the interrelations between Crassulacean acid metabolism, photosynthesis, and respiration. Oxygen exchange of leaf slices was measured polarographically. It was found that the photosynthetic utilization of stored malic acid resulted in a net evolution of oxygen. This oxygen production, and the decrease in acid content of the leaf tissue, were completely inhibited by amytal, although the rate of respiratory oxygen uptake was hardly affected by the presence of this inhibitor of mitochondrial electron transport. Other poisons of respiration (cyanide) and of the tricarboxylic acid cycle (trifluoroacetate, 2-diethyl malonate) also were effective in preventing acid-dependent oxygen evolution. It is concluded that the mobilization of stored acids during light-dependent deacidification of the leaves depends on the operation of the tricarboxylic acid cycle and of the electron transport of the mitochondria. A comparison of enzyme activities in extracts from Aloe leaves and from other plants and studies of leaf anatomy and chloroplast morphology revealed typical characteristics of C(3)−, as well as C(4)−, plants in Aloe.